Canadian Annual Review of Politics and Public Affairs : 1992 - Leyton-Brown, David (Book collections on Project MUSE., 1998)
The year 1992 witnessed a slow recovery from recession, widespread reductions in government spending, and changes in social policy. Dominating the political agenda was constitutional reform. The federal and provincial governments achieved agreement on the Charlottetown Accord, a complex package of constitutional reforms. The Accord received the support of almost all political parties as well as the Canadian media and political elite, only to be overwhelming rejected by the public in a national referendum. On the international front this was the year that Canada signed the North American Free Trade Agreement. Featuring essays on parliament and politics, Ottawa and the provinces, and external affairs, the Canadian Annual Review of Politics and Public Affairs provides a comprehensive account of the year's events. The Canadian Annual Review has long been praised for its excellence. Known for its accuracy, readability, and insight, it offers a synoptic appraisal of the year's crises, controversies, and developments from both federal and provincial perspectives.